ONTOLOGY OF COMPUTATIONAL EXPERIMENT ORGANIZATION IN PROBLEMS OF SEARCHING AND SORTING - Osipova, О.В.; Osipova, Н.В. (Journal of Information Technologies in Education (ITE), 2011)
Ontologies are a key technology of semantic processing of knowledge. We examine a methodology of ontology’s usage for the organization of computational experiment in problems of searching and sorting in studies of the course "Basics of algorithms and programming".